Individual as producer and consumer - Zenović Ivona; Glumac Lourenco Snježana (Megatrend Revija, 2024)
In modern economic theory and practice, the individual occupies a central place as a key actor in the processes of production and consumption. Understanding the role and behavior of the individual in these spheres is essential for explaining and predicting economic flows at the micro and macro levels. An individual as a producer refers to his role in the process of creating economic goods and services. In classical economic theory, production is seen as a combination of three basic factors: labor, capital and land (natural resources). The individual represents labor power, that is, the source of labor as a production input. However, contemporary economic perspectives increasingly emphasize the role of human capital, which includes the knowledge, skills and creativity of the individual. Thus, the individual is no longer just a mere source of physical labor, but also of intellectual and creative contribution to the production process. This paper aims to provide a comprehensive analysis of the individual in his roles as producer and consumer, looking at various economic theories and empirical evidence. It also aims to critically analyze the phenomenon of consumer society and the position of the individual within it, with special reference to the inherent contradiction between the proclaimed individual freedom of choice and the actual subordination to the logic of capitalist production and profit accumulation.